Early predictors of small‐for‐gestational‐age neonates using non‐invasive, low‐cost, and readily available hematological markers. Issue 3 (26th June 2020) - Levy, Ofir; Pariente, Gali; Rotem, Reut; Yohai, David; Weintraub, Adi Y.
Abstract: Objective: To evaluate whether neutrophil‐to‐lymphocyte ratio (NLR), a well‐established inflammatory marker, can be used as an early predictor for small‐for‐gestational‐age (SGA) neonates and other adverse pregnancy outcomes. Methods: A case‐control study compared first‐trimester hematological biomarkers in pregnancies of patients with and without SGA (n=149, n=151, respectively). Demographic, clinical, and obstetrical characteristics and first‐trimester complete blood count were retrieved. Woman with singleton pregnancies who delivered at Soroka University Medical Center between January 2015 and December 2016 were included. Patients with known maternal infections, relevant medications, hematological conditions, and chronic diseases that may alter the blood count, those with multiple pregnancies, and those with congenital or chromosomal abnormalities were excluded. After univariate analysis, a linear regression model was constructed to assess the association between hematological indices and SGA. Receiver operating curves were constructed to evaluate the sensitivity and specificity of NLR. Results: First‐trimester NLR values of the SGA group were significantly higher compared to controls (3.03 ± 1.68 vs 2.63 ± 1.2, P =0.016). Significantly higher levels of NLR were noted among the severely (<3%) SGA neonates (3.12 ± 1.62 vs 2.62 ± 1.2; P =0.034). Conclusion: NLR may be an early, clinically useful marker in the prediction of SGA. As blood samples are routinely collected, correct implication of this result may serve as a valuable non‐invasive, low‐cost, readily available predicting tool. Abstract : Higher neutrophil‐to‐lymphocyte ratio may be a first trimester indicator for small‐for‐gestational‐age neonates.